Scanning for global greenhouse gas emissions reduction targets and their distributions - Stefan P. Schleicher; Angela Köppl (Fondazione Eni Enrico Mattei (FEEM), 2012)
If dangerous and irreversible climatic events are to be avoided, global average temperature should not increase by more than 2êC above pre-industrial levels. In order to achieve such a global target, a mitigation pathway has to limit global emissions to about 50 percent below 1990 levels by 2050. We want to investigate in this paper the radical change of the energy system that would be needed for entering the pathway for halving emission levels by applying a global analytical tool. A comprehensive data base with a global coverage including socio-economic data as well as data on energy and emissions has been set up. By dividing the world into six countries and regions which account for two thirds of global emissions and a region for the rest of the world we investigate in an analytical framework the key drivers and parameters of the energy system which refer to population dynamics, economic activity, energy and carbon intensity. Based on assumptions about the diffusion and convergence of these key parameters we derive implications for long-term emission reduction targets.
Keywords: Q54; Q47; 330; Greenhouse Gas Emissions Reduction Targets; Energy Forecasts